Need Analysis of Animalia Learning Media for Class X at MA Miftahul Ulum Suren Jember After the Covid-19 Pandemic - Sofyan, Moch; Nasution, Nanda Eska Anugrah (META: Journal of Science and Technological Education, 2022)
This study aimed to investigate the degree of urgency of students' needs for Animalia learning media for class X students at MA Miftahul Ulum Suren Jember after the Covid-19 Pandemic. This study is a preliminary study from research and development (R&D) that is carried out if there is a need for development. This study is confined to an analysis of requirements obtained from early field observations as well as a review of relevant literature. The data that has been obtained will be analyzed descriptively. The interview findings revealed that the tenth-grade teacher required learning media on animalia that were comprehensive, more practical, and capable of assisting pupils in overcoming difficulties, particularly in the aftermath of the Covid-19 Pandemic. The results of this study concluded that there is an urgent need for Animalia learning media at MA Miftahul Ulum Suren Jember after the Covid-19 Pandemic.